EV driver characteristics: Evidence from Hawaii. (March 2020) - Wee, Sherilyn; Coffman, Makena; Allen, Scott
Abstract: Electric vehicles (EVs) offer an opportunity to dramatically decrease greenhouse gas emissions within the transport sector if fueled by renewable energy. Hawaii had been early-on considered an ideal place to launch new EVs because of the limited driving range of its island geography. Though it ranks second in new EV registrations per capita in the U.S., still the highest penetrations of EVs on the road at the zipcode level is 4%. This study identifies differences in zipcode EV registrations through 2018 using demographic and transportation behavior characteristics, as well as fuel prices and charging infrastructure. We find that income and level of education are positive and statistically significantly related to zipcode EV registrations. A zipcode with a $10, 000 higher median income is associated with 8% more registered EVs, and a 1000 person increase in the population with a Bachelor's degree or higher is associated with 19% more registered EVs. While all public charging infrastructure is found to have a positive and statistically significant relationship to EV registrations, the magnitude is larger for fast charging stations (Level 3). Lastly, we find that trip distance is not linearly related to EV adoption, where zipcodes with shorter (under 20 min) and longer commute distances (45 min and more) are associated with fewer EV registrations. Highlights: The highest penetration of EVs by zipcode in Hawaii is 4%. Higher income and education are associated with more EV registrations. Public charging infrastructure is positively related to EV registrations. Fast charging (Level 3) has a greater impact than Levels 1 and 2. Shorter and longer commute times are associated with fewer EV registrations.